2017
DOI: 10.2147/ijn.s139625
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interactions between antimicrobial peptides derived from plectasin and lipid nanocapsules containing monolaurin as a cosurfactant against <em>Staphylococcus aureus</em>

Abstract: Development of effective antibacterial agents for the treatment of infections caused by Gram-positive bacteria resistant to existing antibiotics, such as methicillin-resistant Staphylococcus aureus (MRSA), is an area of intensive research. In this work, the antibacterial efficacy of two antimicrobial peptides derived from plectasin, AP114 and AP138, used alone and in combination with monolaurin-lipid nanocapsules (ML-LNCs) was evaluated. Several interesting findings emerged from the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 46 publications
1
32
1
1
Order By: Relevance
“…25 Recently, the MICs of plectasin derivatives against 14 studied strains was determined by Umerska et al and the MICs of AP138 varied 16-fold (range 0.125-4 µg/mL). 26 This is in good agreement with previously reported data showing that the antibacterial spectrum of AP138 includes staphylococci such as MRSA. 20 Garbacz et al reported that the MICs of AMPs for 215 isolates of SA from cystic fibrosis patients varied from 4 to 256 µg/mL.…”
Section: Antibacterial Activity Of Formulationssupporting
confidence: 93%
“…25 Recently, the MICs of plectasin derivatives against 14 studied strains was determined by Umerska et al and the MICs of AP138 varied 16-fold (range 0.125-4 µg/mL). 26 This is in good agreement with previously reported data showing that the antibacterial spectrum of AP138 includes staphylococci such as MRSA. 20 Garbacz et al reported that the MICs of AMPs for 215 isolates of SA from cystic fibrosis patients varied from 4 to 256 µg/mL.…”
Section: Antibacterial Activity Of Formulationssupporting
confidence: 93%
“…Similar to our findings, loading into nanocarriers has been shown to affect the antibacterial activity of loaded compounds, such as antimicrobial peptides [ 38 , 39 ]. Interestingly, the employment of nanocarriers with antibacterial properties, such as monolaurin -LNCs, which showed potent activity against Staphylococcus aureus , resulted in synergistic interactions with peptides derived from plectasin [ 25 ], which is a promising strategy for other compounds such as antipsychotic drugs.…”
Section: Resultsmentioning
confidence: 99%
“…The drug contents were analyzed using an HPLC system previously described [ 25 ]. Briefly, standard solutions of the drugs (0.1–1000 μg/ml) were prepared in deionized water, and 20 μl of the standard or sample were injected into the SymmetryShield TM RP 18 5 μm 4.6x250 mm column (Waters, USA).…”
Section: Methodsmentioning
confidence: 99%
“…[79,99] β-sheet mixed secondary structure when they inhibit bacterial cell wall biosynthesis. [80] Novamycin (34, NP339) is an antifungal peptide being evaluated by Novabiotics. The 14-mer arginine cationic peptide induces membrane disruption of Aspergillus spp.…”
Section: Preclinical Trialmentioning
confidence: 99%
“…Both 40‐amino acid peptides have similar structural characteristics including amphipathic, macrocyclic, and disulfide bonds, except for the extent of the net positive charge. AP114 and AP138 also exhibit α‐helical and β‐sheet mixed secondary structure when they inhibit bacterial cell wall biosynthesis …”
Section: Introductionmentioning
confidence: 99%